A Multi-Organ-on-Chip Approach to Investigate How Oral Exposure to Metals Can Cause Systemic Toxicity Leading to Langerhans Cell Activation in Skin - Koning, Jasper J.; Rodrigues Neves, Charlotte T.; Schimek, Katharina; Thon, Maria; Spiekstra, Sander W.; Waaijman, Taco; de Gruijl, Tanja D.; Gibbs, Susan (Frontiers in Toxicology, 2022)
Investigating systemic toxicity in vitro is still a huge challenge. Here a multi-organ-on-chip approach is presented, using as a showcase topical exposure of oral mucosa to metals, which are known to activate the immune system and in turn may result in skin inflammation. Reconstructed human gingiva (RHG) and reconstructed human skin containing MUTZ-3 derived Langerhans Cells in the epidermis (RHS-LC) were incorporated into a HUMIMIC Chip3plus, connected by dynamic flow and cultured for a total period of 72 hours. Three independent experiments were performed each with an intra-experiment replicate in order to assess donor and technical variation. After an initial culture period of 24 hours to enable stable dynamic culture conditions to be achieved, nickel sulphate was applied topically to RHG for 24 hours and LC activation (maturation and migration) was determined in RHS-LC after an additional 24 hour incubation time. Stable dynamic culture of RHG and RHS-LC was achieved as indicated by assessment of glucose uptake, and lactate production and lactate dehydrogenase release into the microfluidics compartment. Nickel exposure resulted in no major histological changes within RHG or RHS-LC, or cytokine release into the microfluidics compartment, but did result in increased activation of LC as observed by increased mRNA levels of CD1a, CD207, HLA-DR and CD86 in the dermal compartment (hydrogel of RHS-LC (PCR). This first study to describe systemic toxicity and immune cell activation in a multi-organ setting can provide a framework for applying to other organoids in the future.